Daya Tarik Budaya Korea dalam Menarik Minat Wisatawan Kuliner: Analisis Pada Café Chingu Bandung - Agoes, Adrian; Fajri, Khoirul; Clarissa, Emia (Manajemen dan Pariwisata, 2025)
The culinary sector in Bandung, particularly Korean-themed cafes like Café Chingu, has experienced significant growth, attracting both local and out-of-town visitors. This study aims to analyse the factors influencing customer visit interest at a Korean-themed café in Bandung, and to examine the influence of its attractiveness in drawing visitors. It is posited that the unique Korean theme and the culinary offerings significantly contribute to visitor interest. This research employed a qualitative research method with a descriptive approach to understand the phenomenon of visitor interest in Café Chingu. Data was collected through semi-structured interviews conducted with five visitors to Café Chingu. These interviews aimed to gather in-depth information regarding the factors influencing their decision to visit and their perceptions of the café's attractiveness. The findings indicate that the main factor that draws visitors to come initially is its unique Korean theme. Yet, the main factors that make visitors want to revisit are the authentic taste of the Korean food and the comfortable and unique atmosphere. The findings suggest that Café Chingu can further optimise its marketing strategies by highlighting its distinctive Korean theme and culinary authenticity to cater to both K-Pop enthusiasts and individuals seeking unique dining experiences. Further research could explore the impact of social media and broader demographic groups to enhance these findings.